An analysis of personal naming in the Moletji area of the Limpopo area : an onomastic approach - Mphela, Kgabo Lawrance (University of Limpopo (Turfloop Campus), 2010)
The aim of this research is to analyse personal naming pertaining to the Bapedi of Moletjie, Limpopo Province. The study has indicated that personal naming is regarded as a very serious matter among the Bapedi of Moletjie; and is in most instances influenced by the context that prevails during the birth of children. Thus, names are given to children taking into account issues such as status, marital wealth, health, biological and social relationships, nature, and the environment. The study concludes by indicating that naming is part and parcel of human existence and is thus going to be with us forever.
Thesis (M.A.) --University of Limpopo, 2010
Keywords: Naming; 910.0140968; Names, Personal -- South Africa; Onomasiology